Improving Preparedness Through Earthquake Disaster Simulation Activities for Elementary School Student - Sri Haryuni; Ani Sutriningsih; Indah Jayani; Susmiati; Erik Irham Lutfi; Devangga Darma Karingga (STIKes Patria Husada Blitar, 2025)
Earthquakes are one of the natural disasters that frequently occur in Indonesia and claim many lives. Kediri City is an earthquake-prone area because it is home to one of the active volcanoes, Kelud Mountain. Children are among the vulnerable groups most at risk of being affected by disasters. Preparedness is important to be provided early to provide understanding and guidance on the appropriate steps to take when a threat occurs to reduce disaster risk. This community service activity aimed to determine the effect of simulation on earthquake disaster preparedness among students of SDN Pojok 2, Kediri City. The method used a pre-experimental one-group pre-test and post-test design. The samples were taken using cluster random sampling and the sample size used was 46 students. The preparedness data were collected using a questionnaire. The data analysis used the Wilcoxon test. The results of the activity showed that the level of preparedness before the disaster simulation was almost entirely low (80.5%), the level of preparedness after the disaster simulation was almost entirely high (86.9%), and there was an effect of simulation on earthquake disaster preparedness among students of SDN Pojok 2, Kediri City (ρ = 0.000). Preparedness simulations have significantly improved elementary school students' disaster preparedness. Therefore, it is hoped that disaster management simulations can be implemented in all schools in Kediri City, with training provided to elementary school teachers.